Addressing transboundary conservation challenges through marine spatial prioritization. Issue 5 (3rd August 2018) - Gissi, Elena; McGowan, Jennifer; Venier, Chiara; Carlo, Davide Di; Musco, Francesco; Menegon, Stefano; Mackelworth, Peter; Agardy, Tundi; Possingham, Hugh
Abstract: The Adriatic and Ionian Region is an important area for both strategic maritime development and biodiversity conservation in the European Union (EU). However, given that both EU and non‐EU countries border the sea, multiple legal and regulatory frameworks operate at different scales, which can hinder the coordinated long‐term sustainable development of the region. Transboundary marine spatial planning can help overcome these challenges by building consensus on planning objectives and making the trade‐offs between biodiversity conservation and its influence on economically important sectors more explicit. We address this challenge by developing and testing 4 spatial prioritization strategies with the decision‐support tool Marxan, which meets targets for biodiversity conservation while minimizing impacts to users. We evaluated these strategies in terms of how priority areas shift under different scales of target setting (e.g., regional vs. country level). We also examined the trade‐off between cost‐efficiency and how equally solutions represent countries and maritime industries ( n = 14) operating in the region with the protection‐equality metric. We found negligible differences in where priority conservation areas were located when we set targets for biodiversity at the regional versus country scale. Conversely, the prospective impacts on industries, when considered as costs to be minimized, were highly divergent across scenarios and biased the placement of protection toward industries located in isolation or where there were few other industries. We recommend underpinning future marine spatial planning efforts in the region through identification of areas of national significance, transboundary areas requiring cooperation between countries, and areas where impacts on maritime industries require careful consideration of the trade‐off between biodiversity conservation and socioeconomic objectives. Abstract : Article impact statement : Spatial conservation prioritization identifies transboundary areas requiring cooperation between countries and maritime industries